2018
DOI: 10.1002/bjs.10840
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the effect of a fibrin sealant patch on pancreatic fistula formation after pancreatoduodenectomy

Abstract: BackgroundThe potential for a fibrin sealant patch to reduce the risk of postoperative pancreatic fistula (POPF) remains uncertain. The aim of this study was to evaluate whether a fibrin sealant patch is able to reduce POPF in patients undergoing pancreatoduodenectomy with pancreatojejunostomy.MethodsIn this multicentre trial, patients undergoing pancreatoduodenectomy were randomized to receive either a fibrin patch (patch group) or no patch (control group), and stratified by gland texture, pancreatic duct siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
1
32
0
1
Order By: Relevance
“…Major complications occurred in 40% of patients, which is comparable to results reported by other prospective series or randomized trials [ 18 20 ]. Rates of pancreatic fistula highly differ in the literature ranging from 2–63% [ 6 , 21 , 22 ]. In our cohort, 28.6% of patients experienced CR-POPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major complications occurred in 40% of patients, which is comparable to results reported by other prospective series or randomized trials [ 18 20 ]. Rates of pancreatic fistula highly differ in the literature ranging from 2–63% [ 6 , 21 , 22 ]. In our cohort, 28.6% of patients experienced CR-POPF.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, post-operative complications and POPF remain a major issue even in high-volume centres [ 21 ]. The local pancreatic and systemic inflammatory response appears to be decisive, showing a strong association of POD3 serum IL-6 and lipase with CR-POPF and severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital mortality rate in departments performing less than 10 pancreatic procedures per year was 12% compared to 8.1% in those with 20-29 procedures and 5.8% in hospitals with at least 30 procedures. Table 1 Rates of complications specific for pancreatic surgery, as described by [2,39] Specific complication PD (%) DP (%) Regarding publications on detailed postoperative mortality and morbidity after PR in Austria, multicentre data were recently reported in one prospective trial and two retrospective registries on pancreatic cancer and neuroendocrine tumour resections [8][9][10]. These publications all included only medium-to high-volume centres, with a resulting postoperative 30-to 90day mortality of 2.4 to 3.5%, showing that pancreatic surgery in specialized Austrian units is performed within internationally accepted safety range.…”
Section: Introductionmentioning
confidence: 99%
“…Two retrospective studies reported that fibrin sealant patches are feasible and safe with 7.4%–20% POPF rates after PD with pancreaticojejunostomy [ 13 , 29 ]. Schindl et al [ 30 ] conducted a multicenter, randomized clinical trial to investigate the effect of using thrombin-coated collagen patches after PD. In the study, the rates of POPF were 63% in the intervention group and 56% in the control group, and clinically relevant POPF rates were 23% in the intervention group and 14% in the control group.…”
Section: Discussionmentioning
confidence: 99%